2017
DOI: 10.1186/s12885-017-3359-5
|View full text |Cite
|
Sign up to set email alerts
|

Disparities of time trends and birth cohort effects on invasive breast cancer incidence in Shanghai and Hong Kong pre- and post-menopausal women

Abstract: BackgroundBreast cancer is the leading cause of cancer morbidity among Shanghai and Hong Kong women, which contributes to 20–25% of new female cancer incidents. This study aimed to describe the temporal trend of breast cancer and interpret the potential effects on the observed secular trends.MethodsCancer incident data were obtained from the cancer registries. Age-standardized incidence rate was computed by the direct method using the World population of 2000. Average annual percentage change (AAPC) in inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We found that Wuhan had a relatively high AAPC of 3.3% annually, consistent with that of other Asian populations, such as in southern Thailand; 21 however, the AAPC in Wuhan is much higher than that of Shanghai (1.7%). 22 Compared with Western countries, AAPC in Wuhan is nearly equal to that in the USA in the early 1980s 23 and to that in Poland during 1990–1996. Nonetheless, decreasing trends were observed in later periods.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Wuhan had a relatively high AAPC of 3.3% annually, consistent with that of other Asian populations, such as in southern Thailand; 21 however, the AAPC in Wuhan is much higher than that of Shanghai (1.7%). 22 Compared with Western countries, AAPC in Wuhan is nearly equal to that in the USA in the early 1980s 23 and to that in Poland during 1990–1996. Nonetheless, decreasing trends were observed in later periods.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is estrogen-related, and it is believed that the policy of one child per family could be partially responsible for the increased incidence of breast cancer among Chinese women. 3 Women who already had one child need to use birth control methods for a long period of time, and in some cases, women had induced abortion when other birth control methods failed. According to the China Health Statistics Yearbook 2016, the most common birth control method for Chinese women at childbearing age is induced abortion (IA), including surgical abortion (SA) and medical abortion (MA).…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer has become the most common cancer and the most common cause of cancer-related mortality among women worldwide [1]. In China, the incidence of breast cancer is increasing annually by 1.7-2.8% from 1976 to 2009 [2], which constitutes a major breast cancer population in Asia due to her large population.…”
Section: Introductionmentioning
confidence: 99%